Are serum bile salt concentrations raised in hyperlipidaemia?. Issue 3 (March 1980) - Beckett, G J; Douglas, J G; Finlayson, N D; Percy-Robb, I W
Abstract : We have studied serum fasting and postprandial primary bile salt concentrations in a group of 10 consecutive hyperlipidaemic subjects. The efficiency of hepatic bile salt clearance in the same subjects was aslo studied using an injected dose of sodium glycocholate. No increase in serum fasting or postprandial concentrations of the primary bile salts were observed and hepatic bile salt clearance was only marginally abnormal in one subject. The presence of hyperlipidaemia does not invalidate the use of serum conjugated bile salt analysis for the detection of liver diseases.